Post-transplantation plasma malondialdehyde is associated with cardiovascular mortality in renal transplant recipients: a prospective cohort study - Yepes-Calderón, Manuela (Nephrol Dial Transplant, 2020)
BACKGROUND: In renal transplant recipients (RTRs), cardiovascular mortality is the most common cause of long-term renal graft loss. Oxidative stress (OS) has been associated with cardiovascular disease and is known to be enhanced in RTRs. We aimed to prospectively investigate whether the concentration of the OS biomarker malondialdehyde (MDA) is associated with long-term risk of cardiovascular mortality in a large cohort of RTRs. METHODS: The plasma MDA concentration was measured using the thiobarbituric acid reaction assay in 604 extensively phenotyped RTRs with a functioning allograft for ≥1 year. The association between MDA and cardiovascular mortality was assessed using Cox proportional hazard regression analyses in the overall cohort and within subgroups according to significant effect modifiers. RESULTS: Median circulating MDA concentration at baseline was 5.38 [interquartile range (IQR) 4.31–6.45] μmol/L. During a follow-up period of 6.4 (IQR 5.6–6.8) years, 110 (18%) RTRs died, with 40% of deaths due to cardiovascular causes. MDA concentration was significantly associated with the risk for cardiovascular mortality {hazard ratio [HR] 1.31 [95% confidence interval (CI) 1.03–1.67] per 1-SD increment}, independent of adjustment for potential confounders, including renal function, immunosuppressive therapy, smoking status and blood pressure. The association between MDA concentration and the risk for cardiovascular mortality was stronger in RTRs with relatively lower plasma ascorbic acid concentrations [≤42.5 µmol/L; HR 1.79 (95% CI 1.30–2.48) per 1-SD increment] or relatively lower estimated glomerular filtration rates [≤45 mL/min/1.73 m(2); HR 2.09 (95% CI 1.45–3.00) per 1-SD increment]. CONCLUSIONS: Circulating MDA concentration is independently associated with long-term risk for cardiovascular mortality, particularly in RTRs with relatively lower ascorbic acid concentrations or renal function. Further studies are warranted to elucidate whether OS-targeted interventions could decrease cardiovascular mortality in RTRs.